BIMBINGAN TERHADAP PENDERITA GANGGUAN JIWA MELALUI KETERAMPILAN KERAJINAN BATIK UNTUK MENINGKATKAN KEMANDIRIAN DI BALAI RSBKL - Kusuma, Raisha; Ayu, Avrilia (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2024)
Mental health is a critical angle in realizing general well-being. Poor mental well-being arises from mental disorders. The objectives of batik guidance activities are 1). Increasing the independence of PPKS at the RSBKL Hall. 2). Skilled, independent, and live a decent life. 3). Providing motivation to PPKS to be able to work and do business. Guidance on batik skills uses descriptive qualitative research methods involving several parties, namely, batik instructors from the Jumputan Budiyono batik group, PPKS with a stable and productive mental condition, as well as monitoring from social guides and institutional social workers. Participants who take part in batik skills activities are PPKS who are considered to be in a stable period. All active participants undergo routine treatment and undertake occupational therapy for a faster recovery process. Consists of training and development stages. The batik skills guidance service program with PPKS at the RSBKL Hall to increase independence in the social life of the community has been implemented as a medium for occupational therapy. There is also program management for batik guidance.